Genetic relationships and evolution of old Chinese garden roses based on SSRs and chromosome diversity. Issue 1 (December 2017) - Tan, Jiongrui; Wang, Jing; Luo, Le; Yu, Chao; Xu, Tingliang; Wu, Yuying; Cheng, Tangren; Wang, Jia; Pan, Huitang; Zhang, Qixiang
Abstract Old Chinese garden roses are the foundation of the modern rose, which is one of the best-selling ornamental plants. However, the horticultural grouping and evolution of old Chinese garden roses are unclear. Simple sequence repeat (SSR) markers were employed to survey genetic diversity in old Chinese garden roses and genetic differentiation was estimated among different rose groups. Fluorescencein situ hybridization was used to study the physical localization of 5 S rDNA genes and a karyotype analysis was performed. The SSR data suggest that old Chinese garden roses could be divided into Old Blush group, Odorata group and Ancient hybrid China group. The Old Blush group had the most primitive karyotype. The Ancient hybrid China group and modern rose had the most evolved karyotypes and the highest genetic diversity. During the evolution of rose cultivars, 5 S rDNA increased in number, partially weakened in signal intensity and exhibited variation in distance from the centromere. In conclusion, rose cultivars evolved from the Old Blush Group to the Odorata group, the Ancient Hybrid China group and the modern rose. This work provides a basis for the collection, identification, conservation and innovation of rose germplasm resources.